Adrenal Hemangioma: Findings at Multidetector CT with Short Review of the Literature - Abou El-Ghar, Mohamed (Hindawi Publishing Corporation, 2011)
We present the computed tomography (CT) imaging findings of a 44-year-old male with incidentally discovered right adrenal hemangioma displaying imaging pattern of nonadenomatous pattern, associated with multiple hepatic hemangiomata using 64-slice multidetector scanner with reviewing published CT imaging findings with short review of the literature.